2017
DOI: 10.1002/ppul.23761
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumomediastinum, emphysema, and pulmonary bullae associated with refractory Mycoplasma pneumoniae pneumonia in a child

Abstract: We report a 21-month-old child with spontaneous pneumomediastinum (PM), emphysema, and pulmonary bullae caused by Mycoplasma pneumonia (M. pneumoniae) pneumonia. The patient presented with stubborn dyspnea and wheezing although received integrated treatment, including anti-infection, anti-inflammation, and intravenous immunoglobulin. This case was unique in that pulmonary bullae kept increasing. PM and emphysema were refractory in our patient, which have been reported as benign and limited. Surgical interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Spontaneous pneumomediastinum is defined as air in the mediastinum without evident causes (eg, traumatic, iatrogenic, hollow organ perforation, gas‐producing infection surgery, or any other interventions) 8 . Numerous reports 24‐56 have demonstrated that several lung infections, mainly influenza, provoke pneumomediastinum. Radiological features are different in influenza pneumonia compared with COVID‐19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID‐19 pneumonia 31,32,35,37,57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous pneumomediastinum is defined as air in the mediastinum without evident causes (eg, traumatic, iatrogenic, hollow organ perforation, gas‐producing infection surgery, or any other interventions) 8 . Numerous reports 24‐56 have demonstrated that several lung infections, mainly influenza, provoke pneumomediastinum. Radiological features are different in influenza pneumonia compared with COVID‐19 and pneumomediastinum is believed to be a much less frequent complication (or never occurs) in COVID‐19 pneumonia 31,32,35,37,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Although pneumomediastinum was reported as a complication of several lung infections, 24‐56 it is possible that alterations induced by SARS‐CoV‐2 infection are more complex. For instance, SARS‐CoV‐2 infects both type I and II pneumocytes, and this may cause damage of the integrity of the alveolar membrane, which may lead to alveolar rupture 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de los factores de riesgo se incluyen personas jóvenes (18-25 años) (12), de sexo masculino (17), con antecedentes de tabaquismo, infección respiratoria reciente (18), asma e hiperreactividad bronquial y enfermedad pulmonar intersticial (3). En estudios realizados en Corea (19) y Portugal (3), los factores más frecuentemente hallados fueron en su orden: tabaquismo activo, infección respiratoria y asma.…”
Section: Auscultación Pulmonar Nunclassified
“…Mycoplasma pneumonias (MP) mainly causes respiratory tract infection, which leads to up to 40 % of community-acquired pneumonia (CAP) in all age groups, and is also the cause of regional epidemics. MP is generally susceptible to all groups, but the harm to children is more serious [1]. At present, MP pneumonia is often treated with macrolide antibiotics, and the 23sRNA gene at 2063 locus has been verified to be their target [2,3].…”
Section: Introductionmentioning
confidence: 99%